علاج التهاب الحشفة والقلفة الفطري بالفلوكونازول - حرفوش أيمن (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسـة أربعة وعشرين مريضاً بالتهاب الحشفـة والقلفـة الفطري فـي مشفى الأسد الجامعي باللاذقيـة فـي الـفترة الـواقعـة بـين عـامـي 2006-2001، حيث تم عـزل فطر Candida Albicans عـند جـميع الـمرضى. أهم الأعراض السريرية عند المرضى كانت: وجـود حرقـة وحكـة مع بقع حمراء حطاطات متقرحـة مع طلاء ابيض وحمامـة شاملـة على جلد الحشفـة والقلفة. أُعطي جميع الـمرضى mg Fluconazol 150 جرعـة وحيدة مساءً لـمـدة أسبوعيـن حيث تراجعت الأعراض السريريـة عند /21/ مريضـاً (87.5%) مـن أصل /24/ مريضاً، احتـاج ثـلاثـة مـرضـى مـصابيـن أيضـاً بـداء السكري لمعالجـة إضافية لمدة عشرة أيام mg Fluconazol 50 حيث حصلنا بعدها على نتيجة إيجابية عندهم. This study includes twenty four patients with fungal balanoposthitis in Al-Assad University Hospital in Lattakia from 1/1/2001 to 1/1/2006. The fungus of candida albicans was isolated in all patients. Most clinical symptoms were: the presence of ardor and pruritus with ulcered papule and leukoplakia and calf on the skin of the glands and the prepuce. All patients took single dose of fluconazole 150 mg in the evening for two week. The symptoms disappeared in /21/ patients (87.5%) of /24/ patients: three patients who have diabetes mellitus needed additional treatment with fluconazole 50 mg for ten days. Thus, we gained positive result.